2021
DOI: 10.3390/ijms221910489
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Bovine-Induced Pluripotent Stem Cells

Abstract: Pluripotent stem cells (PSCs) have been successfully developed in many species. However, the establishment of bovine-induced pluripotent stem cells (biPSCs) has been challenging. Here we report the generation of biPSCs from bovine mesenchymal stem cells (bMSCs) by overexpression of lysine-specific demethylase 4A (KDM4A) and the other reprogramming factors OCT4, SOX2, KLF4, cMYC, LIN28, and NANOG (KdOSKMLN). These biPSCs exhibited silenced transgene expression at passage 10, and had prolonged self-renewal capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Additionally, EPZ004777 increased blastocyst rate of porcine cell somatic cell nuclear transfer (SCNT) ( Tao et al, 2017 ). EPZ004777 in combination with a WNT inhibitor was insufficient to reprogram notoriously refractory bovine mesenchymal stem cells to iPSCs, but could induce morphological changes ( Su et al, 2021 ). Thus overwhelming evidence indicates that H3K79me is a barrier for pluripotency acquisition across cell types and species ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, EPZ004777 increased blastocyst rate of porcine cell somatic cell nuclear transfer (SCNT) ( Tao et al, 2017 ). EPZ004777 in combination with a WNT inhibitor was insufficient to reprogram notoriously refractory bovine mesenchymal stem cells to iPSCs, but could induce morphological changes ( Su et al, 2021 ). Thus overwhelming evidence indicates that H3K79me is a barrier for pluripotency acquisition across cell types and species ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the process of establishing pluripotent stem cell lines from relevant species such as cow [75], pig [55,76], goat [77], horse [78], and sheep [66,79] has progressed, it is still not at the large-scale level that is needed for the CM production bioprocess. However, there are promising studies such as those by Amilon et al in which they generated functional skeletal myotubes from equine iPSCs [80,81].…”
Section: Mammalian Ipscsmentioning
confidence: 99%
“…Bovine adult fibroblasts were only produced when nanog, SV40largeT, and KDM4A were expressed in combination with the other reprogramming ingredients [ 102 ]. By utilizing a specific component such as SV 40 large T, Lin28, and hTERT sheep somatic cells can be directly transformed to become induced pluripotent stem cell [ 103 , 104 ]. Another study reported the creation of live piglets using the iPSC technology in 2013 [ 13 ].…”
Section: Clean Meat Productionmentioning
confidence: 99%